Indicators of the effectiveness of the healthcare financing system in the Western Balkan countries – critical analysis - Stojić, Vladislava; Eraković, Jevto; Eraković, Nela (Vojnosanitetski pregled, 2022)
Background/Aim. The main objective of the health system is to preserve and improve the general level of health of the population. Every country is making considerable efforts to ensure a sustainable healthcare financing system that would enable the qualitative realization of basic social security rights, rights to healthcare. The aim of the study was to determine the difference between the health system and the concepts of financing through the critical analysis of the system/model and indicators of financing health care in the Western Balkan countries. Methods. An overview of the current state of the health care system in the Western Balkan countries was based on data collected from sources such as the World Bank, World Health Organization, United Nations Development Programme (UNDP) reports, health ministries, finance ministries and statistical institutes of all countries in the analysis. Following the classification of the data, some categories were created to identify differences and similarities between the funding methods used in the Western Balkan countries. The analysis was performed by measuring the effect of healthcare funding on variables by measuring performance. Because it is impossible to measure the relationship between variables in a single regression analysis model, several regression functions were used for accurately determining the relationship results. Results. The two indicators: a total expenditure on health services and institutions as a percent of gross domestic product (GDP), and health expenditure per capita shows weak positive correlation (p = 0.3) indicating that a higher amount of GDP per capita does not have a positive impact on the percentage of health expenditure in the Western Balkan countries observed. Despite differences in expenditures, all countries had a relatively similar funding method with different regulation that has impact on effectiveness of health system and resources used. Conclusion. The health sector in the Western Balkans is characterized by a lack of adequate administrative resources, legislation and regulations, as well as significant constraints in securing the necessary budget. Considering the resources devoted to the health sector in the Balkan countries, it can be said that the authorities in these countries do not see the health system as an important pillar of the country’s development, as they do not devote sufficient financial resources to ensure the functioning of the health system.